1997
DOI: 10.1200/jco.1997.15.3.908
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil plus racemic leucovorin versus fluorouracil combined with the pure l-isomer of leucovorin for the treatment of advanced colorectal cancer: a randomized phase III study.

Abstract: The combination of FU/l-LV produced response rates, response durations, and survival times similar to those with FU/d,l-LV. Biochemical modulation of FU by either pure l-LV or racemic LV thus appears to result in equivalent clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…Regarding the l-LV dose in the present regimen, we selected a fixed dose of 25 mg/body rather than 20 mg/m 2 , not only because the optimal concentration of LV to effectively modulate 5-FU varies substantially depending on the experimental system but also because l-LV has been shown to be clinically equivalent to either the same or a double dose of d,l-LV in its antitumor activity against colon cancer. 23,24 A recent randomized phase II study revealed that oxaliplatin, a 1,2-diaminocyclohexane platinum compound, in combination with CPT-11, has equivalent clinical activity to other 5-FU-based combinations, with manageable toxicity. 25 Moreover, oxaliplatin, in combination with 5-FU/LV (FOLFOX4), has demonstrated superiority over oxaliplatin/CPT-11 (IROX) or CPT-11/5-FU/LV (Saltz) in terms of the toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the l-LV dose in the present regimen, we selected a fixed dose of 25 mg/body rather than 20 mg/m 2 , not only because the optimal concentration of LV to effectively modulate 5-FU varies substantially depending on the experimental system but also because l-LV has been shown to be clinically equivalent to either the same or a double dose of d,l-LV in its antitumor activity against colon cancer. 23,24 A recent randomized phase II study revealed that oxaliplatin, a 1,2-diaminocyclohexane platinum compound, in combination with CPT-11, has equivalent clinical activity to other 5-FU-based combinations, with manageable toxicity. 25 Moreover, oxaliplatin, in combination with 5-FU/LV (FOLFOX4), has demonstrated superiority over oxaliplatin/CPT-11 (IROX) or CPT-11/5-FU/LV (Saltz) in terms of the toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
“…Although intermittent rather than 'essentially uninterrupted use of chemotherapy until progression or death' seems more likely to achieve this goal of palliative tumour therapy, the latter therapeutic strategy is commonly used, at least in the large majority of reported clinical trials in solid tumours, including advanced colorectal cancer. Although in several recently published (European) trials, the duration of treatment has generally been limited to six courses/months, with or without the option to continue treatment when clinical benefit was perceived (Kohne-Womper et al, 1990, British Journal of Cancer (1998) 78(6), [760][761][762][763][764] Reinduction therapy in colorectal cancer 763 1992; Scheithauer et al, 1994Scheithauer et al, , 1997Stoffregen et al, 1996;Zalcberg et al, 1996;Rougier et al, 1997), or to 4 or 12 weeks in patients achieving CR or CR/PR/SD (Labianca et al, 1991;Jager et al, 1996), and occasionally was to be restarted for tumour progression (Kohne-Womper et al, 1990;Scheithauer et al, 1994;Stoffregen et al, 1996;Jager et al, 1996), the therapeutic outcome in patients receiving reinduction has not been reported. As there is virtually no information on the optimal duration of chemotherapy in advanced colorectal cancer in the medical literature, the present study was undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a prospective evaluation including all patients from two treatment centres who had achieved complete response (CR), partial response (PR) or stable disease (SD) after 6 months of firstline chemotherapy with 5-fluorouracil plus racemic leucovorin (LV) or 5-FU plus the 1-isomer of leucovorin (LLV) in a randomized phase III study that has been reported previously (Scheithauer et al, 1997). As defined in the original study protocol, patients eligible for reinduction had to have histologically confirmed metastatic or recurrent colorectal cancer, bidimensionally measurable and progressive disease, a World Health Organization (WHO) performance status score of 0 to 3, an adequate bone marrow reserve (leucocyte count > 3500 tl ', platelet count > 100 000 gl-1) and adequate renal (serum creatinine concentration < 132 ltmol) and hepatic functions (serum bilirubin level < 34 gmol 1-' and serum transaminase level <100 IU 1-').…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two randomised trials have compared the standard racemic leucovorin (d,l-leucovorin with the levorotatory isomer l-leucovorin, and found them to yield similar response rates and survival when combined with uorouracil (134,135). Only l-leucovorin is transformed into active folate cofactors.…”
Section: Fluorouracil In Combination With Leuco×orinmentioning
confidence: 99%